A high school replication of targeted professional development for classroom management - Freeman, Jennifer; Kowitt, Jennifer; Simonsen, Brandi; Wei, Yan; Dooley, Kate; Gordon, Lola; Maddock, Eleanor (Remedial and Special Education, 2018)
In areas of emerging research, such as supporting teachers' classroom management, replication of research is critical to ensuring that recommendations for the field are based on sound science and appropriate for the contexts to which they are being applied. This article describes a replication of research on efficient professional development supports for teachers' classroom managements in a new context: high school classrooms. Data did not support a functional relation between teachers' use of specific praise and the targeted professional development and self-management in the high school setting. Results of this study highlight the critical importance of replication in education research. Based on our findings and our experience conducting this study, we suggest several possible adaptations may be necessary for successful replication at the high school level.
Keywords: behavior; dept.rdg; dept.sed; inservice training; management; peer-reviewed; personnel preparation; research methodology; secondary; single-subject; staff development/inservice

Higher education and disability: A systematic review of assessment instruments designed for students, faculty, and staff - Lombardi, Allison; Gelbar, Nicholas; Dukes, III, Lyman L.; Kowitt, Jennifer; Wei, Yan; Madaus, Joseph; Lalor, Adam R.; Faggella-Luby, Michael (Journal of Diversity in Higher Education, 2018)
In this study, the literature in disability and higher education was examined, with a specific focus on assessment instruments. Published articles (n = 203) on development of new or refinement of existing instruments were reviewed for traits measured and psychometric rigor reported. Findings showed instruments are intended for professionals and students, and of the student instruments, broad categories are academic, nonacademic, and specific to a disability diagnosis. Not all instruments are limited to students with disabilities; many of the reviewed instruments can be utilized in higher-education settings on all students, faculty, and staff, regardless of disability. The implications of the findings undergird the urgency to prioritize disability as a facet of diversity within higher-education scholarship, and furthermore aid this prioritization by providing a catalogue of robust instruments to researchers and practitioners.
Keywords: Disability; assessment; campus climate; dept.rdg; dept.sed; peer-reviewed; program evaluation